2021
DOI: 10.1080/21655979.2021.1969177
|View full text |Cite
|
Sign up to set email alerts
|

Design and characterization of small-diameter tissue-engineered blood vessels constructed by electrospun polyurethane-core and gelatin-shell coaxial fiber

Abstract: Substitution or bypass is the most effective treatment for vascular occlusive diseases.The demand for artificial blood vessels has seen an unprecedented rise due to the limited supply of autologous blood vessels. Tissue engineering is the best approach to provide artificial blood vessels. In this study, a new type of small-diameter artificial blood vessel with good mechanical and biological properties was designed by using electrospinning coaxial fibers. Four groups of coaxial fibers vascular membranes having … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…H&E staining showed the homogeneously implanted collagen and muscle fibers in the wound in light pink and red, which could not be used to distinguish the collagen components and muscle fibers. We can distinguish collagen fibers from muscle fibers by MT staining because this method can stain muscle fibers red and collagen and gelatin fibers blue . MT staining showed that the collagen and gelatin contained in the implants were more homogeneous and showed a greater degree of aggregation and continuity than the collagen newly produced in the wound (Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…H&E staining showed the homogeneously implanted collagen and muscle fibers in the wound in light pink and red, which could not be used to distinguish the collagen components and muscle fibers. We can distinguish collagen fibers from muscle fibers by MT staining because this method can stain muscle fibers red and collagen and gelatin fibers blue . MT staining showed that the collagen and gelatin contained in the implants were more homogeneous and showed a greater degree of aggregation and continuity than the collagen newly produced in the wound (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…We can distinguish collagen fibers from muscle fibers by MT staining because this method can stain muscle fibers red and collagen and gelatin fibers blue. 64 MT staining showed that the collagen and gelatin contained in the implants were more homogeneous and showed a greater degree of aggregation and continuity than the collagen newly produced in the wound (Figure 11). We can distinguish the implanted collagen from the native collagen based on these characteristics.…”
Section: Biomimetic Multilayer Implants Enhanced Angiogenesis In Vivomentioning
confidence: 99%
“…After implantation, ideal small‐caliber tissue‐engineered blood arteries should be able to form new functional tissues. Furthermore, in vivo regenerated vascular grafts should have the structure and function of MSCs and ECs similar to the autogenous artery 52,53 . Graft leakage can occur throughout the graft length and can be stopped by hemostatic compression after re‐establishing blood flow.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in vivo regenerated vascular grafts should have the structure and function of MSCs and ECs similar to the autogenous artery. 52,53 Graft leakage can occur throughout the graft length and can be stopped by hemostatic compression after re-establishing blood flow. In addition, mechanical deterioration caused by host cell recellularization and polymer imbalance on vascular grafts may also lead to graft leakage and expansion.…”
Section: Discussionmentioning
confidence: 99%
“…Fibrous scaffolds prepared by electrospinning are capable of mimicking the complex structure of a natural extracellular matrix ( Hasan et al, 2014 ; Ingavle and Kent, 2014 ; Kishan and Hernandez, 2017 ; Zong et al, 2018 ; Eilenberg et al, 2020 ), and they have large specific surface areas and a high-porosity microstructures that facilitate cell and nutrient infiltration ( Yin et al, 2020a ; Guo et al, 2022 ). The method of coaxial electrospinning can prepare functional fiber membranes ( Ezhilarasu et al, 2019 ; Johnson et al, 2021 ; Zhang et al, 2021 ). Materials can be loaded inside the fiber to enhance the mechanical properties or regulate material degradation.…”
Section: Introductionmentioning
confidence: 99%